Feminist avant-garde: art of the 1970s : the Sammlung Verbund Collection, Vienna - Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); Palais des beaux-arts (Bruxelles, Belgique); Mjellby konstmuseum; Hamburger Kunsthalle; Photographers' Gallery; Museum Moderner Kunst (Autriche); Sammlung Verbund.; Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); et al. (Prestel, 2016)
Featuring a wide variety of work from artists both well-known and under the radar, this dynamic book reveals how women artists reclaimed control of the feminine image in photography, video, and performance art. This book documents a tectonic change in the way women portray themselves in art. Historically, women were depicted as a projection of male fantasies, prejudices, and relationships. However in the 1970s, for the first time, female artists began collectively to investigate visual representations of their own selves. They studied their own bodies and created the prospect of determined feminine identities. Editor Gabriele Schor explores the Feminist Avant-Garde to emphasize the role that these artists played for the last four decades. The works are provocative, radical, poetic, ironic, angry, cynical and heartfelt. The artists shared a collective consciousness that reassessed, and even rejected, what came before, turning to new ways of expression in the fields of photography, performance, film, and video. The collection SAMMLUNG VERBUND founded in 2004 in Vienna focuses on the feminist art movement of the 1970s as one of the main areas and is with 500 works the largest collection with this emphasis. Included are works by Eleanor Antin, Cindy Sherman, Ana Mendieta, Nil Yalter, Ketty La Rocca, Birgit Jürgenssen, Renate Bertlmann, Francesca Woodman and others. This important book emphasizes the accomplishments of women artists who have made a name for themselves while encouraging the young generation.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; biographie; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Chair à canons: Photographie, discours, féminisme - Solomon-Godeau, Abigail; Poupard, Laure; Jones, Julie (Éditions Textuel, 2016)
a 4e de couverture indique : [L'auteure] est aujourd'hui l'une des plus importantes théoriciennes de la photographie. Historienne de l'art, critique et professeur émérite à l'université de Californie à Santa Barbara, ses travaux portent principalement sur la théorie du genre, les études féministes, la culture visuelle en France au XIXe siècle, l'histoire de la photographie et l'art contemporain. ... le présent recueil réunit pour la première fois en langue française un ensemble d'essais parmi les plus significatifs de cette auteure majeure. ... l'ouvrage propose une première partie sur les discours de l'histoire de la photographie, une deuxième sur les pratiques documentaires et une troisième sur la représentation du féminin.
Section: 1 v. (252 p.) : couv. illustrations ; 21 cm
Keywords: 1900-1999; Photographie documentaire; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire de la photographie; histoire et politique; photographie; premier cycle; périodes historiques; représentation des femme*; thématiques